The Choice of Hip Arthroplasty: HRA or THA? Revealed by Meta‐Analysis - Xiao Fan; Yimin Zhou; Tianyu Zhou; Justin P. Cobb; Tengbo Yu (Orthopaedic Surgery)
ABSTRACT Background Total hip arthroplasty (THA) is the gold standard for end‐stage hip arthrosis, while hip resurfacing arthroplasty (HRA) is considered a more bone‐conserving alternative. This meta‐analysis aimed to compare the safety and clinical efficacy of HRA and THA. Methods The databases of PubMed, EMBASE, Cochrane Library, and CNKI were searched for RCTs comparing HRA and THA in treating hip arthrosis from database initiation to April 2024. Inclusion and exclusion criteria were defined, and data extraction, quality evaluation, and risk bias assessment were performed. A meta‐analysis was conducted using appropriate RevManv5.4 and Stata v14.0 software. Results Twenty RCTs from six countries were included. HRA had a similar revision rate, function scores (WOMAC, HSS, OHS, UCLA activity score, EQ‐D, EQ‐5D VAS), and blood levels of cobalt and chromium compared to THA. HRA had fewer complications and less blood loss but required more operating time. Conclusions HRA is a safe and effective alternative to THA, with similar revision and functional outcomes, less blood loss, and is particularly suitable for young male patients with a demand for high‐level activities.